The Investment Strategy of Global Sovereign Wealth Funds During the Period of the Pandemic (COVID-19) - Benyakoub, Maroua; Elias Elhannani, Farah (Finance and Business Economies Review, 2022)
This study aims to determine the extent of the contribution of sovereign wealth funds during the COVID-19 crisis, and its ability to continue post-Covid and to remedy the changes in the economic environment resulting from the outbreak of the epidemic.The most important results reached in general, included the application of sovereign wealth funds to different strategies by allocating huge expenditures to the investment activity that contrast between mitigating and adapting to global economic changes and seizing opportunities to enhance returns on its investment portfolios and the growth of investment in biotechnology was noticeably higher than the rest of the industries, as it financed research and development for the manufacture of respirators and supported the development of vaccines.